Fibroblast growth factor-21 (FGF21) analogs as possible treatment options for diabetes mellitus in veterinary patients - Corbee, Ronald J.; van Everdingen, Dion L.; Kooistra, Hans S.; Penning, Louis C. (Frontiers in Veterinary Science, 2023)
Fibroblast growth factors (FGFs) are involved in numerous metabolic processes. The endocrine subfamily of FGFs, consisting of FGF19, FGF21, and FGF23, might have beneficial effects in the treatment of diabetes mellitus (DM) and/or obesity. The analogue with the greatest potential, FGF21, lowers blood glucose levels, improves insulin sensitivity, and induces weight loss in several animal models. In this review we summarize recent (pre)clinical findings with FGF21analogues in animal models and men. Furthermore, possible applications of FGF21 analogues for cats with DM will be discussed.